Neonatal hearing screening in a low-risk maternity hospital in São Paulo state - Kemp,Adriana Aparecida Tahara (2015)
ABSTRACT INTRODUCTION: The literature indicates that neonatal hearing screening should be universal, so a description of programs that adopt this recommendation is relevant. OBJECTIVE: To describe the results of newborn hearing screening and the profile of mothers and newborns attended to in a low-risk maternity setting, and to correlate the characteristics of this population with the results of transient evoked otoacoustic emissions. METHODS: A contemporary cross-sectional cohort study. The sample consisted of 670 infants and the procedures performed were audiological history, transient-evoked otoacoustic emissions (TEOAE), distortion product-evoked otoacoustic emissions (DPEOAE), and automated-brainstem auditory evoked potential (ABSAEP). RESULTS: The rate of success in this program was 98.5%, the failure rate was 0.62%, and that of non-attendance to finalize the diagnostic process, 0.93%. When correlating the variables studied with the results of transient evoked otoacoustic emissions, there was a significant negative correlation only for age of infant. CONCLUSION: The program of this maternity hospital was effective and complies with national and international recommendations. The population consisted of young mothers with few pregnancy complications and healthy infants. The only variable that influenced transient evoked otoacoustic emission results, after hospital discharge, was the age at which infants were evaluated.